Pharmacological Activity of Honeybush (Cyclopia intermedia) in Boar Spermatozoa during Semen Storage and under Oxidative Stress - Ros-Santaella, José Luis; Kadlec, Martin; Pintus, Eliana (Animals, 2020)
In recent decades, an increasing number of ethnopharmacological studies have been dedicated to medicinal plants from South African fynbos. Among these plants, honeybush (Cyclopia spp.) has become a popular tea, mainly due to its healthy properties and caffeine-free status. The antioxidant, antimutagenic, and antimicrobial properties of this plant have been reported in several cell types, but its effects on reproductive function are still unknown. Here, we assessed the effects of honeybush (Cyclopia intermedia) on boar sperm parameters under induced oxidative stress (Fe2+/ascorbate) and during five days of semen storage at 17 °C without oxidative stress. In both experiments, four concentrations (200, 50, 12.5, and 3.125 µg/mL) of fermented honeybush were tested. Our results show that honeybush enhances sperm parameters, and no toxic effects were observed at any of the tested extract concentrations. Interestingly, honeybush (12.5 µg/mL) improved the sperm motility and kinetic parameters, preserved the plasma membrane integrity, and reduced the lipid peroxidation in the samples exposed to Fe2+/ascorbate (p < 0.05). In the stored samples, positive effects of honeybush on sperm parameters (motility, kinetics, acrosome, and mitochondria) were observed from 48 h until 120 h of semen storage (p < 0.05). Our results clearly show the protective effects of honeybush on sperm samples, thus promoting its use as a natural source of antioxidants for boar semen.
Keywords: semen storage; Cyclopia intermedia; lipid peroxidation; oxidative stress; sperm function